1976
DOI: 10.1039/f19767201377
|View full text |Cite
|
Sign up to set email alerts
|

One-electron reduction potentials of substituted nitroimidazoles measured by pulse radiolysis

Abstract: The differences between the one-electron reduction potentials at pH 7 (E:) of a quinone couple (Q/Q-), and seventeen nitroimidazole couples ( S / S -) were estimated for S = substituted 2-, 4-, and 5-nitroimidazoles, by measuring the equilibrium constant Kc of the reaction S-+ Q + S + Q-. The radical-ions Sand Qwere generated by pulse radiolysis, and their concentrations measured spectrophotometrically after the equilibrium was attained (typically 1-50 ps after the pulse). Estimated values of E:(S/S-) range fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(46 citation statements)
references
References 2 publications
1
45
0
Order By: Relevance
“…These radicals can participate in one-electron transfer equilibria P~NO%-+ Q i2 P~N O Z + Q-(34) which allow the measurements of one-electron redox potentials. Such measurements were carried out with a large number of aromatic and heterocyclic nitro compounds (19,20,23), using as references various quinones and hipyridinium ions. A nitro compound cannot serve as a reference for another nitro compound since the electron transfer reactions PhN& + Ph'N02 PhN02 + Ph'N6%- nism of radiosensitization was sumested to involve one-eleca t high pH or X = OH at lower pH values (pK, = 11.4).…”
Section: Redox Properties Of Nitro Anion Radicalsmentioning
confidence: 99%
“…These radicals can participate in one-electron transfer equilibria P~NO%-+ Q i2 P~N O Z + Q-(34) which allow the measurements of one-electron redox potentials. Such measurements were carried out with a large number of aromatic and heterocyclic nitro compounds (19,20,23), using as references various quinones and hipyridinium ions. A nitro compound cannot serve as a reference for another nitro compound since the electron transfer reactions PhN& + Ph'N02 PhN02 + Ph'N6%- nism of radiosensitization was sumested to involve one-eleca t high pH or X = OH at lower pH values (pK, = 11.4).…”
Section: Redox Properties Of Nitro Anion Radicalsmentioning
confidence: 99%
“…The time scale of this "repair" is similar to the initial repair of radiation sub-lethal damage (SLD) at 37°C, but, whereas repair of SLD is inhibited by heating at 41WC between doses (Ben-Hur and Elkind, 1 974a; Stratford, unpublished), repair of toxicity damage is not. It has been suggested that *Electron affinity has been related to one electron reduction potential, E71, measured by pulse radiolysis (Wardman and Clarke, 1976b (Wong et al, 1978) and a decrease in Do . The present data would suggest that misonidazole-induced damage is not related to radiation-induced sublethal damage and that drug/radiation interaction must occur via other processes.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxygenated solutions in propan-2-ol/5 mm aqueous phosphate buffer (pH 7) (1:3 v/v) containing 10 to 40 gM DPE and 30 to 90 gM 1,1'-butano-2,2'-bipyridinium dibromide (E' -635 mV in aqueous phosphate buffer [1]) were irradiated with electron pulses as described by Wardman and Clarke (29). Rather low concentrations of redox compounds were used in these measurements owing to the low solubilities of the DPEs.…”
Section: Measurements Of One-electron Reduction Potentialsmentioning
confidence: 99%
“…The one-electron reduction potentials of DPEs were measured from the equilibrium concentrations of the reduced and oxidized forms after pulse radiolysis (29) in the presence of 1,1'-butano-2,2'-bipyridinium dibromide. Deoxygenated solutions in propan-2-ol/5 mm aqueous phosphate buffer (pH 7) (1:3 v/v) containing 10 to 40 gM DPE and 30 to 90 gM 1,1'-butano-2,2'-bipyridinium dibromide (E' -635 mV in aqueous phosphate buffer [1]) were irradiated with electron pulses as described by Wardman and Clarke (29).…”
Section: Measurements Of One-electron Reduction Potentialsmentioning
confidence: 99%